A Supply Chain Approach to Mapping the Distribution of Marine Catch: A Case Study on the Constraints of Wonorejo Fishing Village - Patriadi, Andi; Saves, Faradlillah (Jurnal Perikanan dan Kelautan, 2023)
This research aims to understand the supply chain of marine catches from fishermen to consumers in the Wonorejo village area. Data was collected through in-depth interviews with three fishermen and two collectors in the area. The findings indicate that the limited number of collectors can significantly impact the distribution of marine catch and, subsequently, the fishermen's income. Moreover, variations in the type of fish caught play a pivotal role in influencing the distribution dynamics within the market. While there's an apparent need for interventions to enhance the supply chain's efficiency and promote a more equitable distribution of income, it's vital to note that this study's limitations, including sample size and geographic scope, necessitate its results to be viewed as preliminary. Future research in a broader setting must confirm and expand upon these findings.